2005
DOI: 10.1157/13072919
|View full text |Cite
|
Sign up to set email alerts
|

Food hypersensitivity in patients with seasonal rhinitis in Ankara

Abstract: FH was the most common (14 %) accompanying allergic disease in patients with SR. SPT with food allergens have limited diagnostic value for food allergy and/or intolerance. Risk factors for developing FH in patients with SR in Turkey were dermatological symptoms, duration of rhinitis > 5 years, duration of rhinitis symptoms > 3 months per year, and SPT reactivity to Corylus avellena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…[10] In our study, in the population with prick test positivity, the incidence of food allergy was found to be 6.7% (sensitivities to different foods were as follows: banana 1%, egg white 0.7%, egg yolk 0.7%, fish 0.3%, orange 0.7%, cocoa 0.3%, peach 2.3% and cow's milk 0.7%). Lower degree of sensitivities to food allergens may be correlated with the study group consisting wholly of adults.…”
mentioning
confidence: 46%
“…[10] In our study, in the population with prick test positivity, the incidence of food allergy was found to be 6.7% (sensitivities to different foods were as follows: banana 1%, egg white 0.7%, egg yolk 0.7%, fish 0.3%, orange 0.7%, cocoa 0.3%, peach 2.3% and cow's milk 0.7%). Lower degree of sensitivities to food allergens may be correlated with the study group consisting wholly of adults.…”
mentioning
confidence: 46%
“…The lifetime prevalence of FA in this age group was 9.5-35% [17]. Of the 774 patients with seasonal allergic rhinitis in Turkey, the prevalence of food allergy was the most common accompanying allergic disease (14%) [18]. In a large population-based study, among 11810 participants life time prevalence of self-reported FA/ non-allergic food hypersensitivity was reported to be 9.5%, however the rate was 0.1% when double-blind, placebo-controlled food challenge tests were performed [19].…”
Section: In Adultsmentioning
confidence: 90%
“…In several studies, the sensitivity to inhalant allergens (pollen, animal dander, epithelia, household dust) has been reported to be higher (50% to 89%) than that in patients with asthma. 8,10,11 The sensitivity to grass has been reported to be 54% to 69% in 2 publications from Turkey. 12,13 In the authors' study, similar sensitivity rates to inhalant allergens were detected in the patients with asthma and allergic rhinitis (asthma, 28%; allergic rhinitis, 31%).…”
Section: Discussionmentioning
confidence: 99%